Governance of Terong Traditional Market In Makassar City For Competitiveness - Arifin, Lukman; Kasmawati, Andi; Cudai, Andi (Indonesian Journal Publisher, 2025)
Traditional This study examines the governance of Terong Traditional Market in Makassar City, one of South Sulawesi’s largest markets. Employing a qualitative phenomenological approach, the research aims to explore current governance practices, identify determinants influencing governance effectiveness, and propose strategies to enhance market competitiveness. Data were gathered through field observations, in-depth interviews with traders, market managers, and government officials, as well as document analysis. The findings reveal that governance at Terong Market is hindered by fragmented institutional coordination, inadequate infrastructure, weak regulatory enforcement, and limited trader participation. Four critical determinants of effective governance emerged: (1) strategic policy alignment, (2) transparency in financial and operational management, (3) adoption of digital technologies, and (4) multi-stakeholder collaboration.To improve competitiveness, five strategic measures are recommended: revitalization of market infrastructure, digitalization of retribution and service systems, reform of management and human resources, trader empowerment through training and financing access, and inclusive stakeholder forums for participatory governance. Additionally, this study proposes a reconceptualization of the classical POAC (Planning, Organizing, Actuating, Controlling) model—replacing “actuating” with “mediating”—and emphasizes participatory monitoring to strengthen accountability.The study contributes to public administration literature by presenting an adaptive governance model that aligns with the socio-economic dynamics of traditional markets in transition.